2021
DOI: 10.1158/1055-9965.epi-20-1702
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Epidemiology of Nasopharyngeal Carcinoma

Abstract: Background: The epidemiology of nasopharyngeal carcinoma (NPC) has long been a source of fascination due to the malignancy's striking geographic distribution, the involvement of the oncogenic Epstein-Barr virus (EBV), the unique association with intake of Chinese-style salt-preserved fish, and etiologic heterogeneity by histologic subtype.Methods: This review summarizes the current epidemiologic literature on NPC, highlighting recent results from our populationbased case-control study in southern China.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
199
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(207 citation statements)
references
References 164 publications
6
199
2
Order By: Relevance
“…We also observed that betel nut chewing was significantly associated with NPC risk. Although three previous studies found no such association [44], a positive association has been reported between betel nut chewing and NPC risk in NPC high-risk families in Taiwan [45]. A modestly increased risk of NPC associated with tobacco smoking has been reported in southern China [46], which is consistent with our study.…”
Section: Discussionsupporting
confidence: 92%
“…We also observed that betel nut chewing was significantly associated with NPC risk. Although three previous studies found no such association [44], a positive association has been reported between betel nut chewing and NPC risk in NPC high-risk families in Taiwan [45]. A modestly increased risk of NPC associated with tobacco smoking has been reported in southern China [46], which is consistent with our study.…”
Section: Discussionsupporting
confidence: 92%
“…Chronic EBV infection of different tissues of mainly epithelial and lymphocytic origin has been associated with malignant diseases such as carcinomas, lymphomas/lymphoproliferative disorders and soft-tissue tumors [17][18][19][20][21]. Geographically, EBV-associated neoplasia is present worldwide but is more frequent in Asia and Africa compared to the Western world [17,[22][23][24][25] with a higher incidence in males than in females [2,26]. Furthermore, different EBV-associated tumor entities present distinct peaks in the disease onset.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive summary concerning the geographic and epidemiologic peculiarities of EBV-associated malignancies is shown in Table 1. South East Asia, North and East Africa [17,22] gastric adenocarcinoma (GC) 1:100,000 ~9% frequently < 60 years worldwide [18,27,28] intrahepatic cholangiocarcinoma (ICC) <0.01:100,000 6.6% 24-68 years South East Asia [23,29,30] Lymphomas and lymphoproliferative disorders chronic active EBV infection (CAEBV) rare 100% 5-31 Asia [31,32] mucocutaneous ulcer unknown 100% >60 years worldwide [25,33] Europe and North America [34,35] extranodal NK/T cell lymphoma (ENKTL) rare 100% 17-89 years Asia [36,37] classical Hodgkin lymphoma (cHL) 0.5:100,000 in Asia 2.3:100,000 in Europe 50-90% depending on the subtype 20-65 worldwide [19] plasmablastic lymphoma 0.1:100,000 80% 7-65 years worldwide [25,38] post-transplant lymphoproliferative disease (PTLD) <1% in bone marrow transplanted up to 30% in small bowel transplanted patients 60-80% children more often affected worldwide [39] angioimmunoblastic T-cell lymphoma (AITL) 0.05-0.2:100,000 ~70% 20-86 years Europe [40][41][42] primary effusion lymphoma rare 70% young adults worldwide [25] Burkitt lymphoma (BL) sporadic 0.15:100,000 <15% 15-40 years worldwide [43] Burkitt lymphoma (BL) endemic 3-6:100,000 >90% 2-20 years Central Africa East Africa [20] diffuse large B-cell lymphoma (DLBCL) 5-7:100,000 Europe ~4% Asia ~15% 50-91 years Asia [24,25,44] Soft-tissue tumors leiomyosarcoma associated with immune suppression rare 100% children and adolescents worldwide [45] EBV + inflammatory follicular dendritic cell sarcoma rare Unknown 8-77 years * worldwide [21,46] * Data from 9 cases.…”
Section: Introductionmentioning
confidence: 99%
“…The temporal trend of the decreasing incidence in NPC observed in the last 20 years in large cities with prevalent Chinese populations, such as Hong Kong and Singapore, may well be linked to reduced consumption of preserved food, especially in young children. These environmental or dietary factors correlate with the finding that second-generation Chinese born in the West have a lower risk of developing NPC compared to first-generation Chinese immigrants in the same countries, although increasing genetic diversity may also play a role [11,12]. It is important to note, however, that the incidence of NPC in China is highly heterogenous with record incidence rates in the south of the country and some of the lowest rates in the world in the northern part.…”
Section: Non-viral Risk Factors 21 Environmental Risk Factorsmentioning
confidence: 73%
“…A total of 22 microRNAs (miR-BARTs) are encoded in the intronic regions of BamHI fragment A rightward transcripts (BARTs) of the EBV genome. These include: miR-BART2 and two microRNA clusters, cluster 1 (miR-BART1, 3,4,5,6,15,16,17) and cluster 2 (miR-BART7, 8,9,10,11,12,13,14,18,19,20,22) based on their locations on the BamHI-A region [40]. EBV miR-BART microRNAs target and repress cellular pro-apoptotic genes, promoting host cell survival through binding and downregulating cellular mRNAs.…”
Section: Virally-mediated Oncogenesismentioning
confidence: 99%